SMALL CITIES AND THE DISSEMINATION OF THE INDUSTRIAL PRODUCTION MODE. A STUDY OF REGIONAL CHARACTER (Brazilian Geographical Journal, 2014)
The proposal developed in this paper is the presentation and analysis of a new idea on the subject of industrialization in the State of São Paulo. The framework, in this case, is carried out by taking small cities in a specific region of the proposed state as basis by the spread of the industrial mode in their respective territorial division of labor, from the perspective of spatial diffusion of industrial production of non-hardened character, ad hoc and selective dissemination, and a particular spatial configuration from the standpoint of territory. Spatial interactions and "jumps on scales" in shaping the business is the basis for the studied dynamic. The spread is taken as a seminal word since it is the genesis, growth and the articulations between the small regional capital, the historical presence of international capital and determinations of industrial locations.Keywords: small cities, industrialization, São Paulo State.